The Role of Social Media and Artificial Intelligence in Shaping Gen-Z Business Trends Based on Islamic Ethical Values - Lola Suci Mayrani; Suci Ramadhani Saragih; Renita Indriani Hasibuan; Najwa Aidila Fitri; Zultoni Lubis (Universitas Medan Area, 2025)
The rapid growth of social media and Artificial Intelligence (AI) has significantly transformed Generation Z (Gen-Z) business practices, particularly in marketing strategies, product innovation, and the formation of digital business trends. This study aims to analyze the role of social media and AI in shaping Gen-Z business trends and to evaluate these practices based on Islamic ethical values. This research employed a qualitative approach with a phenomenological design through in-depth interviews with 12 Gen-Z digital entrepreneurs, supported by digital observation of social media activities and documentation of promotional content and AI usage. The findings reveal that TikTok and Instagram are the most dominant platforms for branding and market interaction through visual communication, storytelling, micro-influencer engagement, and edutainment marketing. In addition, AI plays a major role in accelerating promotional content production, assisting market trend research, improving design and product presentation quality, developing audience-based branding strategies, and reducing digital marketing operational costs. However, the study also identifies ethical challenges such as AI-based visual manipulation of products, overclaim marketing, influencer promotion without advertising transparency, viral-based business trends lacking sustainability, and increasing digital consumerism leading to hedonistic culture. In conclusion, social media and AI create a dynamic and innovative Gen-Z business ecosystem, yet the integration of Islamic ethical values such as honesty, trustworthiness, transparency, and social responsibility is essential to ensure that digital business practices remain sustainable, fair, and aligned with Islamic moral principles